Association of Plasma Vitamin B6 With Coronary Heart Disease in Patients Undergoing Diagnostic Coronary Angiography: New Insight on Sex Differences - Hu, Lihua; Li, Yuxi; Liu, Zhihao; Fan, Fangfang; Xu, Benjamin; Xu, Richard; Song, Yun; Chen, Ping; Wei, Yaping; Jia, Jia; Zhang, Long; Weng, Haoyu; et al. (Frontiers in Cardiovascular Medicine, 2021)
Aim: To date, findings on the overall and sex-specific effects of plasma pyridoxal 5'-phosphate (PLP, active coenzyme form of vitamin B6) on the risk of coronary heart disease (CHD) have been inconsistent. This study sought to advance our understanding on the association of plasma PLP with risk of CHD, with particular attention paid to sex differences and effect modifiers. Methods: We conducted a hospital-based, case-control study on suspected CHD patients undergoing diagnostic coronary angiography. A total of 429 CHD cases and 429 controls matched by age, sex, and operation time were included in the final analysis. Plasma PLP was assessed using LC-MS. Logistic regression analyses were performed to evaluate the association between plasma PLP and a first CHD event. Results: The mean (SD) plasma PLP levels were 8.4 (6.3) in male cases and 9.0 (11.0) in female cases, and 9.5 (8.5) in male controls and 12.5 (12.9) in female controls. Each 1 ng/mL increment in log2PLP was associated with a 28% lower risk of CHD in overall population. When stratified by sex, plasma PLP was significantly and independently associated with CHD in women (OR = 0.63, 95% CI: 0.50-0.80), but not in men (OR = 0.86, 95% CI: 0.67-1.09). The association of plasma PLP with CHD risk was modified by sex (adjusted Pinteraction = 0.022). Conclusions: We found a significant, inverse linear association between plasma PLP and CHD in Chinese women, but not in men. Our findings warrant additional investigation.